Spiritual Needs among Patients with Mental Disorders: A Scoping Review - Suryani, Suryani; Rafiyah, Imas (Universitas Aisyah Pringsewu, 2023)
The problem of mental disorders is currently an unresolved health problem, mental status that is not handled properly has the potential to cause relapse in people with mental disorders (ODGJ). Spiritual needs as human needs such as ODGJ patients that are fulfilled can provide strength in facing a problem. The purpose of this study is to explore the spiritual needs of patients with mental disorders. The design in this study used scoping review. Keywords used are